Analisa Pengaruh Destination Image dan Motivation Terhadap Tourist Loyalty dengan Perceived Value dan Tourist Satisfaction sebagai Mediasi di Kota Batam - Lily Purwianti; Evelyn Patricia (Universitas Internasional Batam, 2021)
The purpose of this study is to analyse the influence of destination image and motivation towards the loyality of tourist in Batam City. This studi use PLS SEM (partial least square structural equation modeling) as data processing application. The findings show that destination image and motivation that are being intervening by perceived value and tourist satisfaction have positive significant influence towards tourist loyality.